Proceso de innovación curricular en la Facultad de Medicina de la Universidad de Chile - Armanet B., Leonor; de Barbieri O., Zulema (Revista Hospital Clínico Universidad de Chile, 2009)
During the year 2006, the Faculty of Medicine started a process of curricular innovation in its eight schools. For that aim it was decided to implement a competency-based curriculum, thus defining a conceptual framework to guide changes. To organize the new systema Central Commission was established, with sub commissions in the units to collect and assure the participation of all relevant actors involved. As a main task for academic formation, it has been restudied and proposed the actualized graduate profiles for each school. A common training that identifies our professionals, constitutes a seal of our Faculty. To achieve the expected changes is essential to have an institutional political framework and the full commitment of the authorities, academic and student community to this project. To give guarantee to the quality and accomplishment of this process is essential; therefore, there must be internal and external controls to monitor each of the stages to be covered with eagerness and success.